Electronic records management strategies by government agencies in Kenya - Limo, Jonathan; Kwanya, Tom; Chepchirchir, Sally (Record and Library Journal, 2019)
Background of the study: Libraries have various challenges in maintaining their existence as information providers. Libraries must have support so that users do not turn to other services, have special strategies to connect themselves, establish good relationships, and provide user loyalty.Purpose: The purpose of this agreement is to describe the promotion strategy as an effort to encourage the loyalty of university library users.Method: The method used in this research is literature study and also uses the author's active participation observation method as a librarian in the university library.Findings: According to the results of research and literature study by the author, various university libraries provide various types of businesses. The results of the author's discussion there are several discussions about the library promotion strategy arrangement published; (1) Discussion of steps and targets in publicizing and promoting information services; (2) determining the promotion goals by specifying the type of user; (3) a budget is issued; (4) selecting the media used for publication and promotion; (5) evaluating various types of media that have been used; (6) the promotion process in terms of human resources, infrastructure, and various types of librarian activities.Conclusion: With the arrangement of the strategic promotion library model, the authors submit an opinion about the college library that provides a promotional strategy as a promotional container and guarantee self-existence.